«Радуйся, Маріє!»: модифікація молитви прослави у Віри Вовк і Павла Тичини - Гаврилюк, Н. (Слово і Час, 2021)
У статті в компаративному аспекті проаналізовано модифікацію
молитви прослави «Радуйся, Маріє!» у поезії В. Вовк і П. Тичини.
З’ясовано, що у Віри Вовк ця молитва має джерела в акафісті до Богородиці та модифікує його, зберігаючи ознаки акафісту (вірш «Радуйся!») або ж надаючи йому ознак куплетної форми («Небесна Синиця»). У П. Тичини звертання «Ой радуйся, Маріє» з вірша «Скорбна
мати» відсилає до сцени Благовіщення і молитви «Ave, Maria» («Радуйся, Маріє, благодаті повна»), що є частиною молитви на розарію.
Попри звертання «Радуйся», твір П. Тичини перейнятий скорботою.
Тоді як у вірші В. Вовк «Успеніє», що розвиває тему вірша П. Тичини, домінує мотив радості. The paper comparatively analyzes the modification of the laudatory prayer “Rejoice, Mary!” in
the poems by V. Vovk and P. Tychyna, The comparison helps to reveal the peculiarities of the
authors’ styles in the modifications of the prayer and makes it possible to see the deep unity of
emigrational and continental literature, The prayer of Vira Vovk has its sources in the akathist
to the Mother of God. In the poem “Rejoice!”, the poetess retains the general structure of the
akathist, modifying some details: she uses twelve lines instead of thirteen and keeps the address
“Rejoice!” not in every line but only in odd numbers. In the poem “Celestial Tit”, the akathist
acquires the features of a verse form, and the address “Rejoice” is present only in the first and
ninth lines. However, the second strophes of the poems “Rejoice!” and “Heavenly Tit” give
grounds to consider these texts as variants of the same work, The works by Vira Vovk show a
combination of images being characteristic of the church akathist to the Mother of God (lilies,
roses, universe of joy, virgin and mother) with individual authorial ones (heavenly forget-menot,
four-leaf clover, sparkling star, chorale of winged, celestial tit).
the address “Oh, rejoice, Mary!” from the poem “the Dolorous Mother” by P. Tychyna
refers to the scene of the Annunciation and the prayer “Ave, Maria” (“Rejoice Mary,
full of grace”), which is part of the rosary prayer. Despite the address “Rejoice”, P. Tychyna’s
poem is imbued with sorrow, The events of the poem take place aft er the Crucifixion, before
the Resurrection, The address “Oh, rejoice” is contrasted with the drama of a mother looking
for a crucified son and also with Ukrainian history and the landscape. In V. Vovk’s piece
“Dormition”, the events take place after the Resurrection, and therefore the Mother of God
is not sad but smiling, full of joy; she merges with the landscape and not contrasts with it.